A spike in malformed chitinozoans announces the Ireviken Ocean Anoxic event in the lower Wenlock - Vancoppenolle, Iris; Emsbo, Poul; McLaughlin, Patrick I.; De Backer, Tim; Klock, Carolina; Calner, Mikael; Cramer, Bradley D.; Munnecke, Axel; Vandenbroucke, Thijs R.A. (Global and Planetary Change, 2026)
The Silurian record is punctuated by several large, positive stable carbon isotope excursions that coincide with extinction events. Increasingly, these events are interpreted as Silurian Ocean Anoxic Events (OAEs). Malformed chitinozoans (extinct organic-walled zooplankton) recently emerged as potential early indicators of these biogeochemical disturbances. This study is part of an integrated research effort testing the hypothesis that increased chitinozoan teratology is a hallmark signature of most of these Silurian OAEs. Here we focus on the Ireviken Event (lower Wenlock; 433 Ma). Examination of more than 500,000 chitinozoan specimens in 74 samples from the well-studied Lusklint 1 outcrop and the complementary Lusklint-1 core (Gotland, Sweden), allowed their classification into normal, abnormal, and potentially abnormal categories. Ratios of normal versus abnormal chitinozoans across the Ireviken Event reveal malformation concentrations 3 to 33 times higher than background levels. Notably, the rise in teratological forms begins below the lowest conodont extinction datums that traditionally define the onset of the extinction event. This extended anomaly suggests that environmental stress, likely related to marine redox instability and metal contamination, preceded the earliest biotic turnover. In vivo teratologic growth is an emerging powerful proxy for identifying original paleo-oceanographic stress. Our findings establish malformed chitinozoans as early harbingers of this pivotal Silurian OAE. By integrating detailed records of teratology with the stratigraphic context of the Ireviken OAE, this study demonstrates that malformations offer a sensitive and underutilized tool for reconstructing the sequence and drivers of Silurian OAEs.
CRIS-Team Scopus Importer:2026-01-26
Keywords: Chitinozoa; Gotland; Ireviken Event; Malformation; Teratology